2013
DOI: 10.1177/0004563213500657
|View full text |Cite
|
Sign up to set email alerts
|

Is serum human epididymis protein 4 ready for prime time?

Abstract: The National Institute for Health and Clinical Excellence (NICE) guidelines have sparked hot debate regarding the role of carbohydrate antigen 125 (CA-125) for ovarian cancer (OC) detection. Recent literature and evidence calls into question the use of CA-125 in diagnostic algorithms, given the better performance of human epididymis protein 4 (HE4) vs. CA-125 to rule OC. This is an important consideration since combined measurements are not cost-effective. The quality of this evidence is, however, threatened b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…A CA125 value above the threshold of 35 kU/L should be followed by an ultrasound scan (US) of the abdomen and pelvis in order to decide if there is a need to urgently refer or not the symptomatic woman to the specialist. Considering that the actual diagnostic sensitivity and specificity of CA125 amount to less than 80% [15] and the disease prevalence in women presenting with symptoms to primary care is 0.23%, the estimated PPV of CA125 results to be <1%, far from 10% value expected by oncologists [8,9]. The Prostate, Lung, Colorectal and Ovarian Cancer Screening Randomized Clinical Trial, enrolling 78,216 women (median follow-up of 12.4 years), showed that screening by CA125 and transvaginal US was unable to provide diagnostic anticipation when compared with usual care [16].…”
Section: Carbohydrate Antigen 125mentioning
confidence: 93%
See 2 more Smart Citations
“…A CA125 value above the threshold of 35 kU/L should be followed by an ultrasound scan (US) of the abdomen and pelvis in order to decide if there is a need to urgently refer or not the symptomatic woman to the specialist. Considering that the actual diagnostic sensitivity and specificity of CA125 amount to less than 80% [15] and the disease prevalence in women presenting with symptoms to primary care is 0.23%, the estimated PPV of CA125 results to be <1%, far from 10% value expected by oncologists [8,9]. The Prostate, Lung, Colorectal and Ovarian Cancer Screening Randomized Clinical Trial, enrolling 78,216 women (median follow-up of 12.4 years), showed that screening by CA125 and transvaginal US was unable to provide diagnostic anticipation when compared with usual care [16].…”
Section: Carbohydrate Antigen 125mentioning
confidence: 93%
“…In general, the early diagnosis of malignancy in the population at risk is challenging, because the very low OvCa incidence (<40 per 100,000 women) compels setting as desirable, for a diagnostic test, a specificity of >99.5% to finally achieve a positive predictive value (PPV) of 10% [8]. This PPV, implying nine false positive test results for each true positive detecting OvCa, is the goal that currently gynecological oncologists consider as cost-effective for a diagnostic test [9].…”
Section: Early Diagnosis Of Ovca: An Unmet Medical Needmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a revision of current guidelines for OC management by including this novel biomarker is expected. This should require an optimization of its interpretation [2,3]. In particular, to preserve the higher diagnostic specificity of HE4 vs. carbohydrate antigen 125 (CA125), investigations sought to identify factors influencing HE4 results [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The RCV concept was first introduced by Harris and Yasaka to identify the change needed between two serial results from the same individual to be statistically significantly different [7]. It has been increasingly popular in laboratory medicine and currently there is a general agreement in considering RCV as the best tool for monitoring, but also for making diagnosis when the RI approach is inadequate [8]. RCV has also been applied to set objective criteria for use in Δ-checking quality control techniques and in autoverification and auto-validation strategies [9].…”
Section: Introductionmentioning
confidence: 99%